Fragmented power: Europe and the global economy - Sapir, André (Brussels, 2007)
"The European Union is the world's largest economic entity, with half a billion people and a gross domestic product slightly larger than the United States. It is the largest exporter, the largest foreign aid donor, the largest source of foreign investment, and a magnet for migrants. But its decision-making powers are often fragmented and ineffective. To date there has been no comprehensive study of European international economic relations. This book fills that gap. It examines the main areas of Europe's foreign economic policy: trade, development, external competition policy, external financial markets, external monetary policy, migration and external energy/environment policy. This book explains why it is time for the EU to wake up to its global responsibilities, and why, in the absence of reform of its governance system, Europe risks remaining a fragmented power."